2017
DOI: 10.20944/preprints201708.0085.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigation into University Students Restoration Experience: The Effects of Perceived Sensory Dimension and Perceived Restorativeness

Abstract: Salutogenic landscape with its health-promoting qualities is a solution for ever-increasing problem of stress for university students as a vulnerable group. Based on nature related theories, natural environments could have a salutary effect on psychological restoration through stress alleviation. There is a body of research on investigating the impact of open green space characteristics for increasing of psychological restoration through framework of attention restoration theory and supportive environment theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 27 publications
0
5
0
5
Order By: Relevance
“…The Serene dimension has been reported in numerous studies as one of the most restorative PSDs (Malekinezhad & Bin Lamit, 2017; Memari et al, 2017; Peschard & Stigsdotter, 2013; Zhu et al, 2022). In this study, it ranked second among the most restorative PSDs and was not significantly different from the highest-scoring dimension, Diverse.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Serene dimension has been reported in numerous studies as one of the most restorative PSDs (Malekinezhad & Bin Lamit, 2017; Memari et al, 2017; Peschard & Stigsdotter, 2013; Zhu et al, 2022). In this study, it ranked second among the most restorative PSDs and was not significantly different from the highest-scoring dimension, Diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Natural is the PSD that embodies the pristine untamed facet of nature, while Cohesive is a world in itself, uninterrupted (Stoltz, 2020). In contrast, Natural has presented a high level of perceived environmental restorativeness in several studies (Malekinezhad & Bin Lamit, 2017; Memari et al, 2017; Peschard & Stigsdotter, 2013). Cohesive and Natural are the closest PSDs to having the untouched appearance of a forest (Grahn & Stigsdotter, 2010), and some authors have suggested that the greater the perception of human intervention in a natural space, usually the lower the preference for it (Carrus et al, 2013; Ulrich, 1983).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como se pudo reflexionar durante la conformación de la galería resultante, el problema podría ser de lo más relevante para la categorización de las DSP en determinadas regiones geográficas. En el caso del MET, la cantidad de escenarios que se obtuvo de la DSP Natural fue muy alta (once fotografías), pero la de Serena, que se ha catalogado consistentemente como la DSP más restaurativa (Peschard y Stisgdotter, 2013;Memari, Pazhouhanfar y Nourtaghani, 2017;Malekinezhad y Bin Lamit, 2017), se redujo solamente a una fotografía. Podría suponerse entonces que las características ecobiológicas particulares del MET vuelvan algunas dimensiones perceptuales más o menos presentes que otras.…”
Section: Discussionunclassified
“…Attitude is defined as an individual's overall assessment of an object, person, or place, and his or her positive or negative feelings about performing a particular behavior [24]. The more positive a person's attitude toward a behavior, the stronger his or her decision to engage in that behavior.…”
Section: Theory Of Planned Behavior (Tpb)mentioning
confidence: 99%